Tuberculous Abscess of the Chest Wall - Sarkar, Nirmal Kanti; Rahman Mia, Md Mofizur (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Chest wall tuberculosis (TB) is a rare form of extrapulmonary TB, especially in an immunocompetent patient. The disease may resemble a pyogenic abscess or tumor. We present a young lady who developed a slowly growing chest wall swelling, proven as tuberculous etiology. J Bangladesh Coll Phys Surg 2022; 40: 136-137